Executorial Power on Certificate of Liability Based on Credit Agreement - Agnis Nova Della (Sultan Agung Notary Law Review, 2021)
The Mortgage Certificate has executorial power in the credit agreement at Bank Mandiri of Semarang City and to identify and examine obstacles in the execution and solutions. This theoretical framework is using the theory of Progressive Theory, Theory of Law Enforcement, Theory of Islamic Justice. The research method was used to obtain data in this study, using an empirical juridical approach, with descriptive analysis research specifications. The results of this study are: (1) The executive power possessed by the Mortgage Certificate is the same as the court's decision which has permanent legal force, this is because the Mortgage Certificate has included an title which reads " For Justice Based On The Almighty God" (2) Obstacles and solutions found in the execution process of mortgage rights at Bank Mandiri of Semarang City include resistance from the executed parties through civil lawsuits, through reporting to the police, through debt acknowledgment deeds, and time mobilization to defend the object of the auction /object of mortgage. (3) The position of the Debtor and Creditor in the Execution of SHT in the credit agreement at the Semarang City of Bank Mandiri, in the Civil Code Article 1320 requires 4 conditions in the agreement.